Π–π Interactions Mediated Pyrene Based Ligand Enhanced Photoresponse in Hybrid Graphene/PbS Quantum Dots Photodetectors. (15th October 2021) - Ahn, Seungbae; Ingrosso, Chiara; Panniello, Annamaria; Striccoli, Marinella; Bianco, Giuseppe Valerio; Agostiano, Angela; Bruno, Giovanni; Curri, Maria Lucia; Vazquez‐Mena, Oscar
Abstract: Hybrid graphene and quantum dots (QDs) photodetectors merge the excellent conductivity and ambipolar electric field sensitivity of graphene, with the unique properties of QDs. The photoresponsivity of these devices depends strongly on the charge transfer at the graphene/QDs interface. Here 1‐pyrene butyric acid (PBA)‐coated PbS QDs with single layer graphene (SLG) are used to investigate the effect of pyrene as a π–π mediator to enhance charge transfer at the SLG/QDs junction under illumination. The surface chemistry at the QD–QD and SLG/QD interface is studied with the conventional tetrabutylammonium iodide (TBAI) QD linker. The hybrid SLG/QD photodetectors with PBA as a SLG‐QD linker demonstrate a photoresponse up to 30% higher than that recorded for devices where only TBAI is used, due to the strong electron coupling between SLG and QDs. Transconductance measurements show that PBA provokes electron depletion in SLG ascribed to the tendency to delocalize the QDs holes, favoring their transfer to SLG. This surface ligand is found to improve the interaction between the QDs light absorbers and the SLG charge collector, leading to an increased photodetection response. This demonstrates that ligand engineering can enhance charge dynamics and boost the performance of the hybrid device. Abstract : Use of pyrene molecule as graphene‐quantum dot (QD) linker in hybrid graphene/QD photodetectors demonstrates a photoresponse up to 30% higher than that recorded for device where only tetrabutylammonium iodide is used. The ligand engineering demonstrates improved interaction between the QDs light absorbers and the graphene charge collector, enhancing charge transfer and thus boosting the performance of the hybrid device.